Mediterranean Diet, Telomere Maintenance and Health Status among Elderly - Virginia Boccardi; Antonietta Esposito; Maria Rosaria Rizzo; Raffaele Marfella; Michelangela Barbieri; Giuseppe Paolisso (2013)
Leukocyte telomere length (LTL) and rate of telomere shortening are known biomarkers of aging while, numerous studies showed that Mediterranean diet (MD) may boost longevity. We studied association between telomere length, telomerase activity and different adherence to MD and its effects on healthy status. The study was conducted in 217 elderly subjects stratified according Mediterranean diet score (MDS) in low adherence (MDS≤3), medium adherence (MDS 4-5) and high adherence (MDS≥6) groups. LTL was measured by quantitative polymerase chain reaction and telomerase activity by a PCR-ELISA protocol. High adherence group showed longer LTL (p = 0.003) and higher telomerase activity (p = 0.013) compared to others. Linear regression analysis including age, gender, smoking habit and MDS showed that MDS was independently associated with LTL (p = 0.024) and telomerase activity levels (p = 0.006). Telomerase activity was independently associated with LTL (p = 0.007) and negatively modulated by inflammation and oxidative stress. Indeed, telomerase levels were associated with healthy status independently of multiple covariates (p = 0.048). These results support a novel role of MD in promoting health-span suggesting that telomere maintenance, rather than LTL variability is the major determinant of healthy status among elderly.